Critical Thermal Maximum Values for Stream Fishes, Including Distinct Populations of Smallmouth Bass. (25th February 2022) - Brewer, Shannon K.; Mollenhauer, Robert; Alexander, Justin; Moore, Desiree
Abstract: Understanding the thermal tolerances of stream fishes, including sport fishes, is important for assessing thermal stressors that are common across the landscape. Our study objectives were to determine the thermal tolerances of 17 stream fishes (15 species and 2 genetically distinct populations of juvenile Smallmouth Bass Micropterus dolomieu : the Neosho subspecies M. dolomieu velox and the Ouachita strain M . sp. cf. dolomieu velox ). Fish were collected from the field and acclimated to laboratory conditions at 20°C or 25°C, with dissolved oxygen maintained above 6 mg/L. We determined the critical thermal maximum (CTM) using an incomplete block design with 9–11 replications for each species. During trials, we increased the water temperature at a rate of 2°C per hour until fish experienced loss of equilibrium. The estimated CTM ranged from 32.43°C to 38.26°C among species. The CTM values differed significantly between taxonomic groups and species, including the genetically distinct populations of Smallmouth Bass. The Neosho subspecies of Smallmouth Bass had a significantly lower thermal tolerance than the Ouachita strain at both acclimation temperatures; however, the magnitude of the difference was about 0.5°C greater at the higher acclimation temperature. Closely related species, including the Bigeye Shiner Notropis boops and Kiamichi Shiner N . ortenburgeri, had significantly different thermal tolerances despite occupying similar riverine locations. Our results suggest that our perceptions of a species' thermal tolerance based on that of closely related species or that of species using similar habitat may be incorrect. Moreover, the differences in thermal tolerances among populations may be an important consideration for conservation and management actions, such as stocking decisions. Laboratory data such as those provided in this study can be integrated with field data to better assess thermal responses of fishes in a changing environment.